Perhitungan Waste Material Pada Proyek Pembangunan Gedung ICU RS Ngudi Waluyo Blitar: Calculation of Waste Material In The ICU Building Construction Project Waluyo Blitar Hospital - Rinengga, Bintang Ardi; Trisiana, Anita; Widiarti, Wiwik Yunarni (Jurnal Rekayasa Sipil dan Lingkungan, 2024)
Abstract Material waste can have a negative impact on building construction projects, especially in the budgeted cost sector. The use of BIM software can help in calculating and optimizing reinforcement work so that excessive material waste does not occur. In this research, building modeling will be carried out using Revit software. The output achieved in processing this data is quantity take-off. The calculation of remaining rebar material in this research uses the Microsoft Excel software program with the aim of finding out the number of rebar mills needed and the combination of cuts in one rebar mill. Structural modeling using BIM Revit aims to determine the shape of the structure in 3D visualization. This visualization makes it easier to model reinforcement, bends, and iron connections. From the modeling results, the take-off amount is obtained. From the results of the Revit take-off quantity, the length of the rod used as a pattern for cutting steel rods 12 meters long is obtained. Next, an analysis of the level of waste and waste costs is carried out. In the construction of the ICU building at Ngudi Waluyo Blitar Regional Hospital, the volume of material for strengthening work was 3,058.57 meters with a total weight of 1,954.88 kg and a waste cost value of IDR 18,888,958. The residual iron content of Ã˜6 was 2.72%, D8 was 0.48%, D10 was 0.04%, D13 was 4.43%, D16 was 0.35%, and D19 was 1.08%. Keywords: Waste material, BIM, quantity take off, waste level and waste cost. Abstrak Waste material dapat memberikan dampak buruk pada proyek pembangunan gedung, terutama pada sektor biaya yang dianggarkan. Penggunaan software BIM dapat membantu dalam perhitungan dan optimalisasi pada pekerjaan penulangan sehingga tidak terjadi waste material yang berlebih. Pada penelitian ini akan dilakukan pemodelan bangunan dengan Software Revit. Output yang dicapai dalam pengolahan data ini adalah Quantity Take Off. Perhitungan waste material pada tulangan besi dalam penelitian menggunakan program bantu software microsoft excel dengan tujuan untuk mengetahui jumlah los besi yang dibutuhkan dan kombinasi pemotongan dalam satu los besi.Pemodelan struktur menggunakan BIM Revit bertujuan untuk mengetahui bentuk struktur dalam visualisasi 3D. Visualisasi ini mempermudah dalam pemodelan tulangan, tekukan, dan sambungan besi. Dari hasil pemodelan didapatkan quantity take off . Dari hasil quantity take off Revit, maka akan didapatkan bar length yang digunakan sebagai pola pemotongan los besi 12 meter. Selanjutnya dilakukan analisa waste level dan waste cost.Pada konstruksi di gedung ICU RS Ngudi Waluyo Blitar volume waste material pada pekerjaan pembesian sebesar 3.058,57 meter dengan total beratnya adalah 1.954,88 kg dengan nilai waste cost sebesar Rp 18.888.958. Adapun waste level pada besi Ã˜6 sebesar 2,72%, D8 sebesar 0,48%, D10 sebesar 0,04%, D13 sebesar 4,43%, D16 sebesar 0,35%, D19 sebesar 1,08%. Kata kunci: Waste material, BIM, quantity take off, waste level dan waste cost.